2008
DOI: 10.1016/j.trstmh.2008.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and musculoskeletal impairment in Rwanda

Abstract: The recently adopted UN Convention on the Rights of Persons with Disabilities acknowledges the need to address social exclusion and poverty of persons with disabilities. However, policy makers, especially in low-income countries, often lack information about the socioeconomic situation of this vulnerable group of society. This study aimed to assess the association between poverty and musculoskeletal impairment (MSI) in Rwanda. A nationwide population-based matched case-control study was undertaken in Rwanda. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 13 publications
3
25
0
1
Order By: Relevance
“…3 A recent survey of the orthopaedic needs of children in Rwanda suggested that 3% were suffering from a musculoskeletal impairment due to infection. 4,5 Nearly two billion children under the age of 18 live in developing countries, and 400 million in the least-developed countries, compared to only 200 million in industrialised countries. 6 If the prevalence of musculoskeletal impairment due to infection across the leastdeveloped countries is similar to that in Rwanda, in these countries alone approximately 12 million children are affected.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…3 A recent survey of the orthopaedic needs of children in Rwanda suggested that 3% were suffering from a musculoskeletal impairment due to infection. 4,5 Nearly two billion children under the age of 18 live in developing countries, and 400 million in the least-developed countries, compared to only 200 million in industrialised countries. 6 If the prevalence of musculoskeletal impairment due to infection across the leastdeveloped countries is similar to that in Rwanda, in these countries alone approximately 12 million children are affected.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Disability can also have a direct impact on employment opportunities: a study undertaken in Sri Lanka in 2001 identified that 90% of persons with disabilities were unemployed (Tudawe, 2001). Another study in Rwanda showed that adults with musculoskeletal impairment were considerably more likely not to be employed than nonimpaired adults (Rischewski, 2008a). In India, research established that the employment rate of male adults with disabilities was considerably lower than of male adults without disabilities (Mitra and Sambamoorthi, 2008).…”
Section: Disability and Povertymentioning
confidence: 99%
“…Poverty when measured by household expenditure suggests that probability of being poor is higher with disability (Mont & Viet Cuong, 2011;Filmer 2008;Hoogeveen, 2005). However, Rischewski et al (2008) do not find any significant relationship between monetary poverty and disability.…”
Section: Poverty: a Cause Or An Effect Of Disability?mentioning
confidence: 78%
“…The literature shows that disabled persons are less employed (Trani and Loeb, 2012;World Bank, 2009;Mete, 2008;Mitra and Sambamoorthi, 2009;Hoogeveen, 2005), and attain lower education (Mont and Viet Cuong, 2011;Trani and Loeb, 2012;World Bank, 2009;Mete, 2008;Rischewski et al, 2008;Hoogeveen, 2005). Furthermore, Palmer et al (2012) and World Bank (2009) find that households with disabled persons own less assets compared to other households, while Trani and Loeb (2012) suggest that there is no such a relationship.…”
Section: Poverty: a Cause Or An Effect Of Disability?mentioning
confidence: 99%